Vera Frenkel: Cartographie d’une pratique / Mapping a Practice. SBC GALLERY OF CONTEMPORARY ART, MONTREAL - Furness, Amy Marshall (Archivaria, 2011)
Vera Frenkel: Cartographie d’une pratique / Mapping a Practice. SBC GALLERY OF CONTEMPORARY ART, MONTREAL. Mounted at the SBC Gallery of Contemporary Art, 2 October–4 December 2010.